A guide to modeling thermoplastic composite manufacturing processes optimizing process variables and tooling design using finite element analysis - Lynam, Corey; Milani, Abbas S. (DeStech Publications, Inc., 2015)
Explains methods and coding to create FEM-based models to optimize process variables and predict dimensional distortions during the manufacture of thermoplastic matrix composite parts. It also offers a step-by-step approach to simulating and predicting the magnitude of distortion via readily available FE codes.